Peningkatan Keterampilan Bagi Nasyiatul ‘Aisyiyah Melalui Kerajinan Tangan dari Limbah Kresek dan Pemasaran Digital - Debby Ummul Hidayah; Ruly Niko Dwi Putra; Ikhsan Setiawan (Ilin Institute, 2020)
The goal to be achieved is to improve the skills of the members of Nasyiatul 'Aisyiyah Purbalingga Regency, as well as to fulfill activities in the economic sector. The method of implementation is carried out by lecturing as well as direct training in making hand skills from used plastic bags. Then proceed with an explanation of how to market products through digital media for example Instagram. The output of this service activity is (1) Members of Nasyiatul 'Aisyiyah have skills in processing used plastic into products that are of value to use, (2) Members of Nasyiatul' Aisyiyah can market their products through social media.